PRESIDENT’S ADDRESS - Kubínová, Lucie (Image Analysis and Stereology, 2016)
Dear colleagues, Let me wish you and our Image Analysis & Stereology Journal all the best in 2016. It is great honour for me to be in charge of the International Society for Stereology (ISS). I would like to thank Eric Pirard for all his tremendous work and effort he has put into ISS activities in past years, together with all members of the ISS Board. I am glad Eric is willing to help me with ISS as „Immediate Past President“. I also rely on close collaboration with Ida Eržen and Marko Kreft, the Editors-in-Chief of Image Analysis & Stereology (IAS), IAS Editorial Board and future ISS Board. I appreciate long-term cooperation between the Image Analysis & Stereology Journal and the International Society for Stereology and I am looking forward to broaden our relationships in the future. As a President of ISS I plan to evoke new activities which would help to make ISS vivid and useful to scientific community. We are planning new courses on stereology, image analysis and related topics run in cooperation with ISS with reduced fee for ISS members, competion for the best PhD thesis using stereology and/or image analysis, ISS history mapping, etc. I welcome your further suggestions and comments. I would like to cordially invite you to become members of the International Society for Stereology (http://stereologysociety.org/membership.html) and to take part in new activities organized by ISS, such as:• Special Session „3D Image Analysis and Stereology in Fluorescence Microscopy“ at ISBI 2016 (in Prague, see http://biomedicalimaging.org/2016/?page_id=768).• Round table discussion on „Stereology and 3D image analysis in microscopy“ to be held at the 16th European Microscopy Congress in Lyon (EMC 2016, see http://www.emc2016.fr/en/scientific-programme/special/stereology).It is my intention to involve young people and fresh ideas in the activities of ISS and in further improvement of IAS. Please contact me at lucie.kubinova@fgu.cas.cz Looking forward to our collaboration, Lucie KubínováPresident of IASDepartment of BiomathematicsInstitute of PhysiologyCzech Academy of SciencesPrague, Czech Republic